PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN PENERIMAAN PESERTA DIDIK BARU DI SMA NEGERI 8 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the desire of researchers to determine the public's perception of the implementation of the admission of new students at SMA Negeri 8 Pekanbaru. The formulation of the problem in this study is: How is the community's perception of the implementation of the admission of new students at SMA Negeri 8 Pekanbaru. The purpose of this study was to determine how the public's perception of the implementation of the admission of new students at SMA Negeri 8 Pekanbaru. The benefit of this research is that for the community this research can be used as a source of information to find out the community's perception of the implementation of the acceptance of new students at SMA Negeri 8 Pekanbaru. This research is a quantitative descriptive study which was conducted at SMA Negeri 8 Pekanbaru from November 2020 to December 2020. The population in this study were all parents of guardians totaling 432 people with a sampling method in the form of purposive sampling. Data collection techniques used in the form of observation, interviews, questionnaires and documentation. The data analysis technique used is descriptive quantitative. The results of the study: Public Perceptions of Implementing the Acceptance of New Students at SMA Negeri 8 Pekanbaru were classified as very good, namely with a percentage of 87.05%, then based on data analysis it can be explained that the public perception of the implementation of the acceptance of new students at SMA Negeri 8 Pekanbaru is said to be Very Good can be seen from the large percentage of its role which is equal to 51% - 100% = Very Good.Key Words: Perception, Society, Implementation, Acceptance of New Students